A facile approach to spinning multifunctional conductive elastomer fibres with nanocarbon fillers. (22nd February 2016) - Seyedin, Shayan; Razal, Joselito M; Innis, Peter C; Wallace, Gordon G
Abstract: Electrically conductive elastomeric fibres prepared using a wet-spinning process are promising materials for intelligent textiles, in particular as a strain sensing component of the fabric. However, these fibres, when reinforced with conducting fillers, typically result in a compromise between mechanical and electrical properties and, ultimately, in the strain sensing functionality. Here we investigate the wet-spinning of polyurethane (PU) fibres with a range of conducting fillers such as carbon black (CB), single-walled carbon nanotubes (SWCNTs), and chemically converted graphene. We show that the electrical and mechanical properties of the composite fibres were strongly dependent on the aspect ratio of the filler and the interaction between the filler and the elastomer. The high aspect ratio SWCNT filler resulted in fibres with the highest electrical properties and reinforcement, while the fibres produced from the low aspect ratio CB had the highest stretchability. Furthermore, PU/SWCNT fibres presented the largest sensing range (up to 60% applied strain) and the most consistent and stable cyclic sensing behaviour. This work provides an understanding of the important factors that influence the production of conductive elastomer fibres by wet-spinning, which can be woven or knitted into textiles for the development of wearable strain sensors.